An Eighteenth-Century Archaeology of Socioeconomics in Historic Bath, NC - Scattergood, Chloe S (East Carolina University, 2023)
Studying the consumer choices of colonial North Carolinians can indicate much about their lives and status. Archaeological excavations of two eighteenth-century warehouses in Historic Bath can tell us about merchants and their clientele. The material from these warehouses suggests notable wealth disparity, not unlike today, in North Carolina's first established town.
Keywords: colonial; merchant; cellar; socioeconomics; commerce; trade; consumerism; mercantilism; east coast; wealth; Economics--North Carolina--Bath--Sociological aspects--History--18th century; Consumer behavior--North Carolina--Bath--History--18th century; Archaeology--North Carolina--Bath--History--18th century